Telework as a Labor Satisfaction Strategy. Findings in Emerging Economies - Gutierrez-Diez, Maria del Carmen; Aguilar, Alma Lilia Sapien; Howlet, Laura Cristina Pinon (European Scientific Journal, ESJ, 2018)
Satisfaction and flexibility at work are fundamental for new generations. Telework is conceptualized as a modality that allows the employee to work from a place other than the traditional office, usually from home, making use of Information and Communication Technologies (ICT). This research seeks to relate job satisfaction and teleworking. After a literature review, a survey was designed and sent to Mexican teleworkers. It was found that although there is a clear relationship between job satisfaction and use of telework modality among these employees, there are still issues to resolve among them. Findings show that it is difficult for workers to obtain a balance between time and space devoted to work while they are at home, and the most complicated activity seems to be finding time to do exercise.